2019
DOI: 10.1186/s40463-019-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottic p16+ squamous cell carcinoma during pregnancy: a case report and review of the literature

Abstract: Background Head and neck cancer during pregnancy is uncommon. Specifically, laryngeal cancer in pregnancy has only been previously reported 10 times. HPV p16+ supraglottic cancer during pregnancy has never been described in the literature prior to this case report. This case is important to report to understand the most effective and safe diagnostic, treatment and follow-up options available for pregnant patients with laryngeal cancer. Case presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Cancer during pregnancy is uncommon, occurring in one out of every thousand pregnancies, making head and neck cancers during pregnancy an especially rare occurrence. Also there is the fact that chemotherapy and radiotherapy that would normally be given to a patient with a T3 N1 M0 supraglottic squamous cell carcinoma, would not be appropriate in a pregnant patient due to their associated maternal and fetal risks [3] . Radiotherapy during pregnancy might cause harm to the developing fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer during pregnancy is uncommon, occurring in one out of every thousand pregnancies, making head and neck cancers during pregnancy an especially rare occurrence. Also there is the fact that chemotherapy and radiotherapy that would normally be given to a patient with a T3 N1 M0 supraglottic squamous cell carcinoma, would not be appropriate in a pregnant patient due to their associated maternal and fetal risks [3] . Radiotherapy during pregnancy might cause harm to the developing fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer during pregnancy is uncommon. Specifically, laryngeal cancer in pregnancy has only been previously reported 10 times [3] . The management of head and neck cancers during pregnancy requires additional pregnancy-related understanding of the aetiological effect of pregnancy on cancer, knowledge of the direct and indirect effects of cancer on pregnancy, and the effect of diagnostic and treatment modalities on pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However HPV status of that patient was not known. Pugi et al, reported a case of HPV positive squamous cell carcinoma of supraglottic larynx in a 33 year old pregnant lady [22] .…”
Section: Discussionmentioning
confidence: 99%